Remittances, FDI and economic growth: the case of South-East European countries - Bucevska, Vesna; Naumoski, Aleksandar (Taylor & Francis, 2023)
South-East European countries rely heavily on remittances and FDI as external sources of financing. Hence, an investigation of the behaviour of remittances and FDI during the business cycle and their impact on economic growth is of crucial importance. To achieve this objective, we first analyse the cyclical nature of remittances and FDI flows in Albania, Bosnia and Herzegovina, Croatia, Montenegro, the Republic of North Macedonia, and Serbia (SEE6) during their business cycles in the 2008q1-2021q2 period. Second, we investigate the causal link among these variables, and find out that although at the aggregate level remittances and FDI move synchronously and in the same direction as the business cycle, there are considerable variations across countries. Following Dumitrescu-Hurlin Panel Granger causality test, we find that for most SEE6 there is a bidirectional causal relationship between remittances and economic growth, i.e. economic growth is caused by remittances, and GDP growth also stimulates remittances.
Keywords: Remittances; foreign direct investment; economic growth; Dumitrescu-Hurlin Granger panel; South-East European countries